Insight into the plasma oxidation process during pulsed laser deposition. Issue 2 (22nd October 2021) - Irimiciuc, Stefan A.; Chertopalov, Sergii; Bulíř, Jiŕí; Vondracek, Martin; Fekete, Ladislav; Jiricek, Petr; Novotný, Michal; Craciun, Valentin; Lancok, Jan
Abstract: The dynamics of transient plasmas generated by ns laser ablation of Ag targets under various O2 gas pressures (10 −5 –10 Pa) were investigated by implementing angle‐ and time‐resolved Langmuir probe (LP) analysis and space‐ and time‐resolved optical emission spectroscopy (OES). The effects of an O2 atmosphere on silver oxide formation and the ionic kinetics and the overall plasma energy were systematically investigated. Measurements performed in the LP floating regime revealed the presence of three‐ionic structures with kinetic energies varying from 0.8 to 350 eV, which can be tailored by the addition of O2 . The time‐modulated regime of electron temperature in the 0.5–3 eV observed for pressures higher than 2 Pa of O2 could be explained by the formation and dissociation of silver oxide molecules. The energetic balance sustains molecular oxide formation, as confirmed by OES measurements, which revealed emission signatures of AgO (B  2 Π3/2 and X  2 Π3/2 ) in the 350 nm (B  2 Π3/2 ) and 460 nm (X  2 Π3/2 ) spectral regions. Finally, thin films were deposited to understand the range of possibilities offered by pulsed laser deposition of Ag in O2 . The morphology and atomic structure of the films were analysed for large‐scale deposition. Silver oxides were detected in the films starting from 2 Pa, while at higher values, we found mixtures of different Ag x O y phases. A cauliflower‐like morphology was dominant above 5 Pa of O2 atmosphere pressures, which signals the formation of the AgO phase in the deposited film. Our results demonstrate that the properties of deposited thin films are influenced by plasma properties. Abstract : Angle‐ and time‐resolved Langmuir probe measurements and optical emission spectroscopy (OES) were performed to monitor the silver oxidation processes during the pulsed laser deposition of Ag x O y . A modulated evolution of electron temperature signals the formation/dissociation of Ag x O y molecules, confirmed by OES, where the signatures of AgO (B  2 Π3/2 ) are observed. The angular distributions of the Ag plasma expanding in O2 are correlated with the phase and morphology of the deposited films.